2014
DOI: 10.1016/j.scitotenv.2014.02.039
|View full text |Cite
|
Sign up to set email alerts
|

Polychlorinated biphenyls and hexachlorocyclohexanes in sediments and fish species from the Napoleon Gulf of Lake Victoria, Uganda

Abstract: • High concentrations of PCBs were found at locations near Jinja Municipality.• The PCB and HCH levels were low to moderate compared to other locations worldwide.• The fish from the Napoleon Gulf was fit for consumption in regard to PCBs and HCHs.• The ratios of α-/γ-HCH were low suggesting past input of lindane. a b s t r a c t a r t i c l e i n f o Polychlorinated biphenyls (PCBs) and hexachlorocyclohexanes (HCHs) were analyzed in surface sediments (b30 cm depth) and two fish species: Nile perch (Lates nilot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
29
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 40 publications
6
29
5
Order By: Relevance
“…Average concentrations of the Σ 18 PCBs ranged from 80 to 779 pg g − 1 wet weight (ww). The concentrations were in the same range as those reported in similar fish species from the Napoleon Gulf of Lake Victoria (94-716 pg g −1 ww: Ssebugere et al, 2013a;Ssebugere et al, 2014) These levels were at least an order of magnitude higher compared to the present results. In Egypt, Said et al (2008) reported PCB concentrations varying from 3320 to 72 060 pg g −1 lw in fish (O. niloticus and Clarias gariepinus) from Lake Burullus.…”
Section: Statistical Data Analysissupporting
confidence: 85%
See 3 more Smart Citations
“…Average concentrations of the Σ 18 PCBs ranged from 80 to 779 pg g − 1 wet weight (ww). The concentrations were in the same range as those reported in similar fish species from the Napoleon Gulf of Lake Victoria (94-716 pg g −1 ww: Ssebugere et al, 2013a;Ssebugere et al, 2014) These levels were at least an order of magnitude higher compared to the present results. In Egypt, Said et al (2008) reported PCB concentrations varying from 3320 to 72 060 pg g −1 lw in fish (O. niloticus and Clarias gariepinus) from Lake Burullus.…”
Section: Statistical Data Analysissupporting
confidence: 85%
“…They were 3-fold higher than those reported in sediments from the Napoleon Gulf and Thurston Bay of Lake Victoria (Ssebugere et al, 2013b;Ssebugere et al, 2014). The PCB concentrations in the present study were comparable to data from other fresh water bodies in Africa: the Nile River in Egypt (El-Kady et al, 2007), Ghar El Melh lagoon in Tunisia (Ameur et al, 2011), Pangani River basin in Tanzania (Hellar-Kihampa et al, 2013) and Congo River basin in the Democratic Republic of Congo (Verhaert et al, 2013).…”
Section: Statistical Data Analysissupporting
confidence: 63%
See 2 more Smart Citations
“…The Shapiro-Wilk test was used for verifying the normality of data. Since concentration values were not normally distributed, the Mann-Whitney U test was used for comparing two data sets (Ssebugere et al, 2014a;Ssebugere et al, 2014b). The comparisons of particle and PCDD/F concentrations during normal days and haze days were tested using this method.…”
Section: Quality Assurance/quality Control and Statistical Analysismentioning
confidence: 99%